ENVIRONMENTAL AND ECONOMIC PERFORMANCE MEASUREMENT THROUGH GREEN SUPPLY CHAIN AND GREEN IN STORE MICRO, SMALL AND MEDIUM ENTERPRISES IN PROBOLINGGO CITY - Ratih Hendayani; Ariel Axton Emmanuel; Indira Rachmawati; Ridwan Purwanadita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Micro, Small and Medium Enterprises or MSMEs are a business group with a very large number in Indonesia. According to the Central Statistics Agency (BPS) the number of Micro, Small and Medium Enterprises (MSMEs) is 64,000,000 MSMEs and the City of Probolinggo has 33,395 MSMEs. Indonesia ranks second in Asia as the country that produces the most plastic waste after China. High waste production and the majority of the MSME industry make it important to implement Green Supply Chain Management.This study aims to determine the impact of the Green in Store Processes dimension on Performance Outcomes through the mediation of the Green Supply Chain Processes dimension with the research object of MSMEs in Probolinggo City.This study uses quantitative methods with multivariate analysis methods in data processing assisted by SmartPLS. Data was collected by distributing questionnaires using a Likert scale as a measurement scale. Data processing in this research is Direct and Indirect using SmartPLS software by carrying out two Bootstrapping processes in one tailed and two-tailed to determine the direct and indirect effects between variables.Based on the results of research conclusions, it is proven that many variables do not have a significant effect. The researcher suggests that the Probolinggo City Government should directly guide MSMEs regarding the implementation of Green Supply Chain Management. Keywords: Green Supply Chain Management, MSMEs, Green in store Processes, Environmental Performance, EconomicPerformance,SmartPLS